I codici corviniani della Biblioteca Estense - Venturi, Anna Rosa (Verbum – Analecta Neolatina, 2022)
The history of the Corvinian books is long and controversial. Their traces have been followed all over the world, so that it has been possible to virtually reconstruct a meaningful portion of the extraordinary collection that Matthias Hunyadi put together. Tracking the origin of the seventeen codices which ended up in the Estense Library is quite simple: they were bought in a single lot by the Duke Alfonso II of Este in Venice. However, today there are only fifteen of them, and they were exhibited in Modena in 2002. They are being examined one more time, with the aim to add some new insight.